IS26 cannot move alone. (4th March 2021) - Harmer, Christopher J; Hall, Ruth M
Abstract: Background: IS 26 plays a major role in the dissemination of antibiotic resistance determinants in Gram-negative bacteria. Objectives: To determine whether insertion sequence IS 26 is able to move alone (simple transposition) or if it exclusively forms cointegrates. Methods: A two-step PCR using outward-facing primers was used to search for circular IS 26 molecules. Gibson assembly was used to clone a synthetic IS 26 containing a catA1 chloramphenicol resistance gene downstream of the tnp26 transposase gene into pUC19. IS activity in a recA − Escherichia coli containing the non-conjugative pUC19-derived IS 26 :: catA1 construct and the conjugative plasmid R388 was detected using a standard mating-out assay. Transconjugants were screened for resistance. Results: Circular IS 26 molecules that would form with a copy-out route were not detected by PCR. The synthetic IS 26 :: catA1 construct formed Cm R Tp R transconjugants (where Cm R and Tp R stand for chloramphenicol resistant and trimethoprim resistant, respectively), representing an R388 derivative carrying the catA1 gene at a frequency of 5.6 × 10 −7 Cm R Tp R transconjugants per Tp R transconjugant, which is comparable to the copy-in activity of the unaltered IS 26 . To test for simple transposition of IS 26 :: catA1 (without the plasmid backbone), 1200 Cm R Tp R colonies were screened and all were resistant to ampicillin, indicating that the pUC19 backbone was present. Hence, IS 26 :: catA1 had only formed cointegrates. Conclusions: IS 26 is unable to move alone and cointegrates are the exclusive end products of the reactions mediated by the IS 26 transposase Tnp26. Consequently, when describing the formation of complex resistance regions, simple 'transposition' of a single IS 26 should not be invoked.